EVALUATION OF THE INCIDENCE OF UROPATHOGENIC BACTERIA AMONG PREGNANT WOMEN ATTENDING ANTENATAL CLINIC DOMA HOSPITAL GOMBE - ISA, SHU’AIBU; MUSTAPHA Y, KABIRU; HAMZA A, JABIR; RASHIDA, SALEH (BIMA JOURNAL OF SCIENCE AND TECHNOLOGY GOMBE, 2022)
Urinary tract infections (UTIs) are common global problems associated with health conditions. Patients suffering from UTIs like other patients with clinical infections are liable to suffer from wide variety of infectious agents. This study evaluates the presence of uropathogenic bacteria so that appropriate measures to curb their menace could be enhanced. A total of 200 urine samples were collected from pregnant women between the ages of ≤20 to 40. CLED (Cystein Lactose Electrolyte Deficient) agar was used for differential isolation of uropathogenic bacteria. Positive samples were subjected to Gram’s staining and biochemical identification to confirm their identities. Socio-demographic factors and clinical information were used to investigate the incidence. Organisms isolated were Escherichia coli, Proteus spp. Citrobacter spp., Klebsiella spp., Pseudomonas aeruginosa, Salmonella spp., Shigella spp., Yersinia enterocolitica and Vibrio spp. with incidences of 54.4%, 12.2%, 10%, 5.6%, 5.6%, 3.3%, 3.3%, 3.3% and 2.2 respectively. In relation to =age group, women at 20 years or less had 50% (n=6/12) incidence, 21-25 years 63.3% (n=38/60), 26-30 years 42.9% (30/70), 31-35 years 34.3% (12/35) and 36-40 years 17.4% (4/23). Socio-demographic factors revealed that the sexually inactive educated women with good hygienic status and with repeated infection were found to have lower uropathogenic prevalence than the sexually active uneducated and unhygienic women with first time infection. E. coli had the highest frequency and Vibrio spp. had the least occurrence. The growth of Vibrio spp. and the other unrelated species to urine may be attributed to the improper hygiene of the pregnant women. The age group with highest incidence was 21-25 years. This may be due to the fact that women in this group are the most sexually active and might have had many previous pregnancies.